A series of Cd(ii) coordination polymers based on flexible bis(triazole) and multicarboxylate ligands: topological diversity, entanglement and properties. Issue 38 (21st September 2017) - Li, Ke; Blatov, Vladislav A.; Fan, Tao; Zheng, Tian-Rui; Zhang, Ya-Qian; Li, Bao-Long; Wu, Bing
Abstract : Eight Cd(ii ) coordination polymers with diverse topologies based on 1, 4-bis(1, 2, 4-triazol-4-ylmethyl)benzene and multicarboxylate ligands were synthesized and characterized. The 3D topologies of1, 2 and3 are unprecedented. Abstract : Eight Cd(ii ) coordination polymers, [Cd(btrb)(H2 O)4 ][Cd2 (btrb)(btec)(H2 O)2 ]2 (OH)2 ·5H2 O n (1 ·(OH)2 ·5H2 O), [Cd(btrb)0.5 (bptc)0.5 ]·H2 O n (2 ·H2 O), [Cd3 (btrb)(btc)2 ]·3H2 O n (3 ·3H2 O), [Cd(btrb)(ip)(H2 O)]·H2 O n (4 ), [Cd(btrb)(MeOip)]·H2 O n (5 ), [Cd2 (btrb)2 (1, 2-bdc)2 ]·3H2 O n (6 ), [Cd2 (btrb)(bpdc)2 ]2 ·11H2 O n (7 ) and [Cd(btrb)(bpdc)]·H2 O n (8 ), were synthesized under hydrothermal conditions.1 shows an unprecedented (4, 4, 4, 4)-connected 3D (electroneutral motif) + 1D (cationic motif) → 3D polythreaded structure. The point symbol of the new 3D motif is (4 6 )2 (8 6 )(4 2 ·8 2 ·10 2 )(4 3 ·8 3 )4, or the secondmot topology based on the [Cd2 (COO)] dimer.2 shows an unprecedented (4, 5, 6)-connected 3D network with a point symbol of (4 2 ·8 4 )(4 7 ·6 3 )2 (4 6 ·6 6 ·8 3 ).3 shows an unprecedented (3, 8)-connected self-catenated 3D network based on the Cd(ii ) trimer cluster [Cd3 (COO)2 ] with a point symbol of (4 2 ·6)2 (4 4 ·6 11 ·7 6 ·8 6 ·9).4 exhibits a 2D + 2D → 2D interpenetration network based on the 2Dsql network.5 exhibits a 4-connected network with acds topology.6 presents the first example of a 2-fold interpenetrating 6-connectedcco-6- Pbcm 3D network with a point symbol of (4 7 ·6 8 ).7 shows a (3, 3, 4, 4)-connected 2D 3, 3, 4, 4L72 network with a point symbol of (3·4·5)(4·8 2 )(3·4·5·8 3 )(3·4·8 2 ·9 2 ).8 presents a (3, 5)-connected self-catenated 2D 3, 5L2 network with a point symbol of (4 2 ·6)(4 2 ·6 7 ·8). The luminescence and thermal stability of1–8 were investigated.